Latent profiles of sleep quality, financial management behaviors, and sexual satisfaction in emerging adult newlywed couples and longitudinal connections with marital satisfaction - Saxey, Matthew T.; Li, Xiaomin; Wikle, Jocelyn S.; Hill, E. Jeffrey; LeBaron-Black, Ashley B.; James, Spencer L.; Brown-Hamlett, Jessica L.; Holmes, Erin K.; Yorgason, Jeremy B. (Frontiers in Psychology, 2022)
Emerging adult newlywed couples often experience many demands on their time, and three common problems may surface as couples try to balance these demands—problems related to finances, sleep, and sex. We used two waves of dyadic data from 1,001 emerging adult newlywed couples to identify four dyadic latent profiles from husbands’ and wives’ financial management behaviors, sexual satisfaction, and sleep quality: Flounderers, Financially Challenged Lovers, Drowsy Budgeters, and Flourishers. We then examined how husbands’ and wives’ marital satisfaction, in relation to profile membership, varied at a later wave. We found that Financially Challenged Lovers and Flourishers had significantly higher marital satisfaction than Drowsy Budgeters and Flounderers (mostly medium effect sizes). Whereas Financially Challenged Lovers and Flourishers did not differ in terms of marital satisfaction, Drowsy Budgeters seemed to have slightly higher marital satisfaction than Flounderers for wives only (small effect size). However, we did not find evidence that these connections meaningfully differed by sex. Clinicians may use these findings to compare the marital satisfaction of emerging adult newlywed clients to their expected profile’s marital satisfaction and intervene accordingly. Clinicians might also consult the differences in marital satisfaction between the profiles when considering interventions in finances, sleep, and sex for these clients. Educators might consider incorporating these findings into curriculum for emerging adult newlywed dyads as descriptive motivation for intentionality with finances, sleep, and sex. Such efforts, according to our findings, might benefit emerging adults’ satisfaction with their new marriages over time.